Hardware and Software: Verification and Testing 11th International Haifa Verification Conference, HVC 2015, Haifa, Israel, November 17-19, 2015, Proceedings - Piterman, Nir.; Piterman, Nir. (Programming and Software Engineering ;, 2015)
This book constitutes the refereed proceedings of the 11th International Haifa Verification Conference, HVC 2015, held in Haifa, Israel, in November 2015. The 17 revised full papers and 4 invited talks presented were carefully reviewed and selected from numerous submissions. The papers are organized in topical sections on hybrid systems; tools; verification of robotics; symbolic execution; model checking; timed systems; SAT solving; multi domain verification; and synthesis.